Commissive Speech Act in the Movie John Wick Chapter 2 - Juniartha, I Wayan - (Lingual Journal of Language and Culture; Vol 10 No 2 (2020): Lingual: Journal of Language and CultureDO - 10.24843/LJLC.2020.v10.i02.p06, 2020)
Commisive is kind of speech acts that used by the speakers to commit themselves to some future course action. They express the speaker’s attention to do something on some future action. This study concerned on finding out types of commissive speech act used by characters in the movie John Wick Chapter 2 , as well as analyzing the meaning of the utterances. This study applied the theory of pragmatics from Yule (1996) to find out the types of commissive speech act, theory of meaning from Thomas (1995) to analyse the implied meaning and supported by the theory of context of situation from Halliday and Hasan (1989). The data were collected by using observation method and analysed by descriptive qualitative method.  The finding is presented in formal and informal way. Our finding shows that there are four types of commisive speech acts which predominantly used by the characters in the movie John Wick Chapter 2 , they are: refusal (12%), warning (48%), promise (12%) and threat (28%).    Keywords: commissive, speech act, utterance, meaning